IMPACT OF THE COVID-19 PANDEMIC ON THE EPIDEMIOLOGY OF AIDS IN BRAZIL: COMPREHENSIVE ANALYSIS FROM 2014 TO 2022 - Francisco Machado Pereira , Antônio; Mendes de Carvalho, Thulio; Maria Andreoli Fellini , Beatriz; de Souza Sabino , Franklin; Abdon Jude Todohlan Savoeda , Jésuton; Nicolle dos Santos Vargas , Gabriela; José da Rocha Silva , Jardeson; Prudêncio Ibiapina de Morais , Victor; Antônia Oliveira Machado Pereira , Maria; de Sousa Alves , Matheus (Health and Society, 2024)
Introduction: The HIV/AIDS epidemic poses a global challenge to public health, exacerbated by the COVID-19 pandemic. Investigating the effects of this health crisis on AIDS epidemiology in Brazil is crucial. Methodology: Epidemiological, descriptive, and retrospective study using SINAN data from 2014 to 2022, totaling 187,947 cases. Quantitative analysis of distribution by sex, age, race, and region. Results: Reduction in cases observed from 2017, more pronounced in men and in the Southeast and South regions. Male predominance (70% of cases). Concentration in the age range of 20 to 49 years (75% of cases). Browns and blacks more affected. Discussion: Integration of different epidemiological dimensions provides a comprehensive overview of the epidemic in Brazil. Highlights the need for tailored public policies, improvement of information systems, and surveillance. Conclusion: Between 2014 and 2022, analysis of AIDS epidemiological data in Brazil reveals a decrease in diagnoses, particularly among men in the Southeast and South, with possible underreporting. Male predominance, concentration of cases among 20 to 49-year-olds, and racial disparities necessitate customized policies. Enhancing information systems is crucial.